Smart Fish Scales Based on The Internet of Things (Case Study at The Bentenge Bulukumba Fish Auction) - Wahidah; Asyraful Insan Asry; Nurzaitun (UPPM Poltek ATI Makassar, 2023)
The fish scales used at fish auctions, especially at the Bentenge Bulukumba fish auction, generally still use analog scales, which only show the weight of the fish being weighed. The aim of this research is to create a digital fish scale based on the Internet of Things (IoT) that can be monitored by Thingspeak. This scale is designed to not only display the weight, but also the name and price of the fish being weighed. This tool uses a NodeMCu ESP32 as a controller, an HX711 loadcell sensor as a weight sensor, Thingspeak and SDCard to store weighing result data, a keypad to select a menu of objects to be weighed, an LCD to display the name, weight and price of the fish. The weighing results can be monitored by fish sales business owners wherever they are. From the results of testing the tool, it was found that the accuracy of the fish weight measurement results was 98.83%, and the accuracy of calculating the price of fish on the SDCard display against the price based on the results of the loadcell sensor scales on the tool was 99.998%. The data from the instrument measurements in the form of the name, weight and price of the fish on the LCD display is in accordance with the data in the form of a graph containing the weight and weighing time sent to the Thingspeak platform, as well as data in the form of the date, weighing time, name, weight and price of the fish stored on the SDCard